Systematic Reviews in Occupational Health and Safety: where are we and where should we go? - Verbeek, Jos; Mattioli, Stefano; Curti, Stefania (La Medicina del Lavoro, 2019)
Systematic Reviews have been introduced to improve the synthesis of available evidence and to reduce bias in the conclusions about a body of evidence. Nowadays, Systematic Review is an established method also in the Occupational Safety and Health (OSH) field. It is the Cochrane Work Review Group that facilitates authors to produce Cochrane reviews of intervention topics in this area. A variety of guidelines used Cochrane Work reviews for underpinning their recommendations. Due to the comprehensive search and reproducibility of the methods of a systematic review, it turned out that systematic reviews can be powerful in changing beliefs. For example, studies published in the eighties advocated the use of back schools. Nowadays, we know that the total body of evidence has changed the traditional view that training in lifting techniques could prevent back pain. ‘Sitting is the new smoking’ is an eye catching nicely alliterating motto, but it is of course highly overstated. The findings of a Cochrane review of the effects of interventions to decrease sitting at work showed that sitting time can be reduced by a bit less than two hours per day by providing sit-stand desks plus education. However, it is unclear if this is sufficient to counter the effects of sitting. A wealth of evidence on OSH interventions has been collected by international collaboration in the Cochrane Work Review Group. This can be extended to systematic reviews of the effects of exposure of workers to assess to which risks of adverse health effects they are exposed.